Development of a reliable trust management model in social internet of things. (1st January 2014) - Panda, Mrutyunjaya; Abraham, Ajith
In this paper, we introduce the first application of the belief propagation algorithm in the design and evaluation of trust management systems with an introduction of a novel paradigm of social internet of things (SIoT), as 'social network of intelligent objects', that are based on the notion of social relationships among objects. Further, we address a trust-making process, where a person needs to make a judgement about the trustworthiness of another community member where they do not have any prior knowledge about each other. Our proposed model uses various performance measures such as: centrality and transitivity measures for SIoT analysis and then employs hybrid fuzzy nearest neighbour with Bayesian belief network and Bayesian belief network with conditional independence to represent a trust-based evaluation. Bayesian belief propagation technique is used here to infer trustworthiness in a social context. Finally, we perform non-parametric Friedman two tail test for statistical significance of the results obtained for various approaches. The evaluation of the model is done on datasets collected from